2016
DOI: 10.1007/s11627-016-9763-8
|View full text |Cite|
|
Sign up to set email alerts
|

Direct somatic embryogenesis and genetic homogeneity assessment of regenerated plants of Anthurium andraeanum Linden cv. Fantasia

Abstract: We present here a method for the in vitro propagation of Anthurium andraeanum cv. Fantasia through direct somatic embryogenesis. The embryos were directly formed at the cut end of most of the leaf explants when cultured on MS basal medium supplemented with N 6 -benzyladenine (BA) plus α-naphthalene acetic acid (NAA). MS basal media supplemented with BA (0.27 μM) and NAA (2.68 μM) induced maximum number of somatic embryos per leaf explant (15.33 ± 1.45) after 28 d of continuous culture. The highest numbers of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 37 publications
0
8
0
3
Order By: Relevance
“…The stages clearly indicated the embryo maturation leading to the formation of shoots (Fig. 2f) (Bhattacharya et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The stages clearly indicated the embryo maturation leading to the formation of shoots (Fig. 2f) (Bhattacharya et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Before inoculation, leaves were cut into 1cm squares, pricked few times with a sterilized scalpel and placed on culture media with the adaxial Bhavana, Satyan and Aswath surface down. The cultures after inoculation were incubated under cool and dark conditions at 25±2.0°C and 70% relative humidity (RH) (Bhattacharya et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…In that study the author found that the NAA auxin at a concentration of 10 μM gave superior results for the establishment of embryogenic calli in nodal segments of the cultivar under study (1.23), expressed as the number of embryogenic calli formed. Bhattacharya et al (2016) achieved the best results for obtaining embryogenic calli from leaf explants in a medium supplemented with NAA (2.68 μM) and BAP -6-benzylaminopurine (0.27 μM). Other authors have been successful in inducing somatic embryos in anthurium with the 2,4-D auxin, such as in the research by Bautista et al (2008) and Bhavana et al (2018).…”
Section: Indução à Embriogênese Somáticamentioning
confidence: 99%
“…In anthurium, 2,4-dichlorophenoxyacetic acid (2,4-D) and naphthaleneacetic acid (NAA) are, in that order, the most commonly used auxins. The most widely used explants are the leaves, but other organs/ tissue can also be used with satisfactory results, such as nodal segments (BAUTISTA et al, 2008;XU et al, 2010;PINHEIRO et al, 2013;PINHEIRO et al, 2014;BHATTACHARYA et al, 2016). Another interesting growth regulator to be studied is the auxin Picloram (4-amino-3,5,6-trichloropyridine-2-carboxylic acid), which also promotes high callus induction (PACHECO et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation